Effectiveness of health education for the prevention of puerperal sepsis to the postnatal mothers admitted in maternity hospital, Thapathali. - Pradhananga, Renuka Devi (2002)
ABSTRACT: Women are susceptible to many complications during puerperium period and their knowledge about postnatal health care is poor. To address this problem, education had been imparted to postnatal discharged mothers. This study was conducted in Maternity Hospital, Thapathali (Postnatal ward unit 11), on the topic of " effectiveness of health education for the prevention of puerperal sepsis." The main objective of this study was to asses the existing knowledge on postpartum care and identify the change in knowledge on postpartum care after health information. Interventional health education programme was conducted purposefully among 100 postnatal discharged mothers using personal communication and visual aid. Study design was a quasi-experimental study, before and after tests (pre-test and post-test) were done to assess their knowledge before and after teaching programme immediately and individually. A semistructured questionnaire consisting of 25 questions about postnatal care components was administered. The finding of this study showed that the majority of respondents (66%) who were admitted in maternity Hospital, Thapathali (postnatal ward unit 11), were urban area, (35%) were illiterate, (58%) belonged to 20-24 years of age group and various ethnic groups. Similarly the majority of respondents (54%) lived in nuclear family. By occupation the majority of respondents (86%) were housewives. The majority (99%) of the respondents had received information on puerperal sepsis, its sign and symptoms, breast feeding help to prevent puerperal sepsis; (91%) of the respondents received information that nutrition plays an important role in prevention of puerperal sepsis; 100% of respondents had received information on reestablishment of sexual relationship after 2-3 months of delivery. All respondents (100 postnatal mothers) had received information on postnatal care components for the prevention of puerperal sepsis. After health education and post-test, I provided brochure for prevention of puerperal sepsis with the postnatal discharge mothers who were literate.